Massive Hemoptysis due to Endotracheal Hemangioma: A Case Report and Literature Review - Yu, Yeonsil; Lee, Suhyeon; An, Jinyoung; Lee, Jeongmin; Kim, Jihoon; Lee, Youngkyung; Jung, Eunah; Song, Sookhee; Kim, Hyeok; Kim, Suhyun (Tuberculosis and respiratory diseases, 2015)
Tracheal hemangioma is a rare benign vascular tumor in adults. We reported a case of massive hemoptysis caused by a cavernous hemangioma in a 75-year-old man. This is the first report, to our knowledge, of a tracheal cavernous hemangioma that presented with massive hemoptysis. The lesion was removed with a CO2 laser under rigid laryngoscopy. Endovascular tumors, such as tracheobronchial hemangiomas, should be considered a diagnostic option in cases of massive hemoptysis without a significant underlying lung lesion.